2004
DOI: 10.1212/01.wnl.0000145764.70698.4e
|View full text |Cite
|
Sign up to set email alerts
|

Visual perception in Parkinson disease dementia and dementia with Lewy bodies

Abstract: Abstract-Objective:To quantify visual discrimination, space-motion, and object-form perception in patients with Parkinson disease dementia (PDD), dementia with Lewy bodies (DLB), and Alzheimer disease (AD). Methods: The authors used a cross-sectional study to compare three demented groups matched for overall dementia severity (PDD: n ϭ 24; DLB: n ϭ 20; AD: n ϭ 23) and two age-, sex-, and education-matched control groups (PD: n ϭ 24, normal controls [NC]: n ϭ 25). Results: Visual perception was globally more im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
177
4
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(197 citation statements)
references
References 45 publications
11
177
4
5
Order By: Relevance
“…The prominent non-dominant hand 9HP score differences between LBD and PD subjects likely reflect the more impaired visuospatial impairments seen in our LBD group [48].…”
Section: Differentiation Of Pd and Lbd Subjects Based On Motor Characmentioning
confidence: 82%
“…The prominent non-dominant hand 9HP score differences between LBD and PD subjects likely reflect the more impaired visuospatial impairments seen in our LBD group [48].…”
Section: Differentiation Of Pd and Lbd Subjects Based On Motor Characmentioning
confidence: 82%
“…10 Visual-spatial abstraction and reasoning were more impaired in patients with PD-D, whereas visual-spatial memory tasks were worse in patients with AD. This was especially evident in more complex tasks that required planning and sequencing.…”
Section: Clinical Featuresmentioning
confidence: 95%
“…Evidence of a visual processing deficit resulting from impairment of the magnocellular system (i.e., an area in the brain that processes visual information about movement) has been hypothesized (Castelo-Branco et al, 2009;Silva et al, 2005), since peripheral vision is known to be altered in PD by an abnormality of dopaminergic amacrine cells (Bodis-Wollner & Paulus, 1999). There has been some support for this hypothesis since studies have shown that those with PD have difficulty identifying the direction or speed of movement when solely relying on moving visual stimuli in their periphery (Mosimann et al, 2004;Trick, Kaskie, & Steinman, 1994) . However, research investigating motion discrimination in PD did not find that the damaged magnocellular pathway was predictive of motion integration deficits (Castelo-Branco et al, 2009).…”
Section: List Of Tablesmentioning
confidence: 99%